Aspects of numerical simulation of failure of elastic-brittle solids - Wildemann, Valeriy Ervinovich; Feklistova, Evgeniya Vyacheslavovna; Mugatarov, Artur Ildarovich; Mullahmetov , Maksim Nikolayevich; Kuchukov, Artur Marsovich (Computational Continuum Mechanics, 2023)
Understanding the nucleation and evolution of microdefects in solid bodies is important to ensure the reliability and safety of critical structures and to identify their strength and deformation resources. In numerical modeling, failure zones can be represented as areas with significantly underestimated rigid characteristics by analogy with the method of variable elastic parameters used in solving the boundary-value problems of the theory of plasticity. However, the formal application of numerical algorithms of plasticity does not always lead to an adequate description of failure processes especially in elastic-brittle bodies. This paper considers some aspects of the numerical simulation of failure processes, such as the calculation of a stress-strain state after reducing the rigidity of finite elements under constant boundary conditions by organizing an appropriate iteration procedure, and the selection of the maximum number of finite elements fractured per iteration, the value of a loading step, and the discretization degree of the computational domain. The influence of the above aspects on the results of failure simulation is illustrated by comparing the numerical solutions to the problem of deformation of the strip made of elastic-brittle material with the edge stress concentrator, which were obtained by different algorithms. The loading diagrams were plotted, and the implementation of the post-critical stage at the macro level was demonstrated. Failure kinetics was analyzed for different variants of implementation of the iterative procedure and at a variable number of elements fractured per iteration. It has been found that, in order to get an accurate description of deformation and failure processes, the automatic selection of a loading step seems to be more reasonable. Analysis has indicated that the discretization degree of the computational domain has a strong impact on the modeling results. This suggests that the finite element size should correspond to a certain strength constant of a material having the dimensions of length.